Potential limits of AAV‐based gene therapy with the use of new transgenes expressing factor IX fusion proteins. Issue 1 (6th December 2018) - Le Quellec, Sandra; Dane, Allison; Enjolras, Nathalie; McIntosh, Jenny; Rosales, Cecilia; Negrier, Claude; Nathwani, Amit
Abstract: Introduction: The variety of treatment for haemophilia B (HB) has recently improved with the emergence of both AAV‐based gene therapy and bioengineered human factor IX (hFIX) molecules with prolonged half‐life due to fusion to either albumin (Alb) or immunoglobulin Fc fragment (Fc). Aim: Adeno‐associated viral vectors (AAV) mediating expression of hFIX‐Alb and hFIX‐Fc fusion proteins was investigated for gene therapy of HB to explore if their extended half‐life translates to higher plasma levels of FIX. Methods: Single‐stranded cross‐packaged AAV2/8 vectors expressing hFIX‐Alb, hFIX‐Fc and hFIX were evaluated in vitro, and in mice. Results: Both hFIX‐Alb and hFIX‐Fc fusion proteins were synthesized and expressed as single chains of expected size following AAV‐mediated gene transfer in vitro and in vivo . The procoagulant properties of these hFIX‐fusion proteins were comparable to wild‐type hFIX. However, their expression levels were threefold lower than wild‐type hFIX in vivo most likely due to inefficient secretion. Conclusion: This, the first, evaluation of hFIX‐fusion proteins in the context of AAV gene transfer suggests that the hFIX‐fusion proteins are secreted inefficiently from the liver, thus preventing their optimal use in gene therapy approaches.